Effect of habitat type on benthic macro invertebrates in two lowland tropical streams, Costa Rica - Ramírez, Alonso (1998)
Benthic macroinvenebrate community structure was studied with respect to stream habitat type in two lowland tropical streams. Three reaches along the Carbón river and two within tile Gandoca stream were chosen as study sites in Talamanca. Costa Rica. Macroinvenebrates were collected from four habitat types: leaf packs in riffles, cobble in rimes, areas of sand in pools, and areas of gravel in pools. Communities were dominated by in sec ts in the orders Ephemeroptera (Thraulodes, Baetis?. Diptera (Chironomidae. (Hydroptilidae, Glossomatidae, Hydroptilidae, Calamoceratidae), and Odonata inseci macroinvertcbrates (Progomphus. Hetarina). Non insect macroinvertebrates were dominated by shrimps (Macrobrachium) and snails (Gastrupoda). Functional feeding group composition was dominated by collector -gatherers. In most reaches, both habila1 types in riffles supported higher macroinvertebrate abundance and biomass than did habitats in pools. Leaf packs in riffles represent an important habitat that is present year-round in these aseasonal tropical systems. Community composition and diversity were similar to that reported for other areas of Central America.